Threads of heritage: Intricate patterns of Indonesia and Kazakhstan - Tassygozhina, Gulmira; Astuti, Kun Setyaning (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
Indonesia and Kazakhstan have a rich cultural heritage expressed through intricate patterns and unique threads of art.Indonesia, a country with a rich history and diverse ethnic composition, is known for its unique traditions in textile arts. The richness and variety of Indonesian fabrics such as batik, as well as techniques and patterns that show the cultural characteristics of different regions of Indonesia is very significant in the heritage of Indonesian culture. Particular attention is paid to the symbolism and historical significance of the patterns, as well as their role in rituals and holidays. On the other hand, Kazakhstan, which located in central Eurasia, also has a rich cultural heritage, including unique textile traditions. The features of Kazakh national patterns that show various aspects of the life of this nation are very important. Particular attention is paid to the symbolism of animals and plants in patterns, as well as their role in preserving cultural identity.Overall, the heritage threads of Indonesia and Kazakhstan represent not only artistic expressions, but also important elements of the cultural and historical heritage of these countries. Studying these patterns helps to better understand and appreciate the diversity and richness of the cultural traditions of these peoples.This study aims to understand how the threads of heritage connected into the patterns of Indonesia and Kazakhstan reflect the cultural, historical and religious aspects of these societies.